Ewolucja perspektywy kultury organizacyjnej w zarządzaniu : od klasyków do współczesnych koncepcji - Pierzchawka, Sylwia (Prospects of organizational culture evolution in management: throughout classics up to contemporary concepts, 2005)
The purpose of this paper is to show cultural attributes evolution from classic management foundations to contemporary management concepts. Moreover, this paper specifies organizational culture attributes needed in current conditions of progressive globalisation and the tendency to a homogenous market. The discussed problems and conclusions are based on the literature.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 28-37